FORMULASI PENGATURAN RUANG TERBUKA HIJAU DALAM PERATURAN DAERAH RENCANA TATA RUANG WILAYAH PROVINSI MALUKU - La Ode Angga (Kajian Hukum, 2017)
The study entitled "Formulation of Green Open Space Arrangement in Local Regulation No.16 of 2013 on Spatial Planning of Maluku Province 2013-2033, with the aim of reconstructing the formulation of open space arrangements in the Provincial RTRW of Maluku Provincial Law, which is regulated in Law No . 26 Year 2007 on Spatial Planning.This research is a juridical-normative research, ie research conducted on the principles of law, the legal principles in the sense of the value (norm) of concrete law and legal system. In this study using several approaches. The approach used in the research is statutory approach and conceptual approach.In conducting Reconstruction Formulation of Green Open Space Arrangement in Local Regulation no. 16 of 2013 on RTRW Maluku Province, the authors refer to the Constitution of the Republic of Indonesia, especially Article 28H paragraph (1) and Article 33 paragraph (4) UUDNRI 1945. In addition, the authors refer to Law no. 26 Year 2007 on Spatial Planning especially Articles 28-31 and 55-58, and refers to the principles and legal theories relevant to spatial planning.Key words : Formulation, Open Green, Bylaw No. RT RW. 16 of  2013